2021
DOI: 10.1002/sus2.17
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose‐based hydrogels regulated by supramolecular chemistry

Abstract: Supramolecular hydrogels based on cellulose attract increasing attention because of their novel structures and broad potential applications. In this review, hydrogels composed of cellulose are summarized according to category of supramolecular interactions in the networks including hydrogen bonds, electrostatic interactions, host‐guest interactions, and others. Supramolecular cellulose‐based hydrogels constructed by noncovalent bonding usually exhibit environmental friendliness, designing flexibility and diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 103 publications
0
21
0
Order By: Relevance
“…After mixing evenly, APS is added to initiate the polymerization reaction (Figure 1a). The association strength of micelles is greatly affected by the polarity of the mixed solution [45][46][47][48]. In general, in a weakly polar solvent, the micellar association is loose.…”
Section: Resultsmentioning
confidence: 99%
“…After mixing evenly, APS is added to initiate the polymerization reaction (Figure 1a). The association strength of micelles is greatly affected by the polarity of the mixed solution [45][46][47][48]. In general, in a weakly polar solvent, the micellar association is loose.…”
Section: Resultsmentioning
confidence: 99%
“…When the hydrogel network is formed using chains connected with chemical bonds, the hydrogels reach an equilibrium swelling state and are called chemical gels. On the other hand, when non-covalent interactions occur, hydrogels are called physical [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural residues, such as cottonseed shell, reed straw, sawdust, corn stalk, bamboo, and bagasse, are produced in large quantities annually. They consist of cellulose, hemicellulose, and lignin and thus have been identified as the most abundant renewable resources. Incorporating PVA with biomass materials is a good solution to prepare biocomposites with better mechanical performance and biodegradability, since the many hydroxyl groups in PVA are keen to form hydrogen bonds with those in the cellulose and hemicellulose, which guarantees the compatibility of PVA and agricultural residues. , For instance, Haque prepared PVA/cotton gin trash (CGT) biocomposite films by the solution-casting method and demonstrated that CGT enhanced the tensile strength and thermal stability. Balavairavan fabricated a series of biodegradable PVA composite films with green banana peel filler (GBPF) and confirmed that the PVA/GBPF biofilms presented better biodegradation properties.…”
Section: Introductionmentioning
confidence: 99%